Assessment of Charged AuNPs: From Synthesis to Innate Immune Recognition. (3rd September 2018) - Rahme, K.; Minassian, G.; Sarkis, M.; Nakhl, M.; El Hage, R.; Souaid, E.; Holmes, J. D.; Ghanem, E.
Abstract : Gold nanoparticle (AuNP) physicochemical characteristics, mainly size and charge, modulate their biodistribution, cytotoxicity, and immunorecognition as reported from in vitro and in vivo studies. While data from in vitro studies could be biased by several factors including activation of cells upon isolation and lack of sera proteins in the microenvironment of primary generated cell lines, in vivo studies are costly and time-consuming and require ethics consideration. In this study, we developed a simple and novel in vivo -like method to test for NP immunorecognition from freshly withdrawn human blood samples. AuNPs with a size range of 30 ± 5 nm coated with cationic poly(L -lysine) (PLL) dendrigraft and slightly negative poly(vinyl alcohol) (PVA) were synthesized in water. PLL-capped AuNPs were further coated with poly(ethylene glycol) (PEG) to obtain nearly neutrally charged PEG-AuNPs. Physicochemical properties were determined using zeta potential measurements, UV-Vis spectroscopy, dynamic light scattering (DLS), and scanning electron microscopy (SEM). Gel electrophoretic separation, zeta potential, and DLS were also used to characterize our NPs after human blood plasma treatment. PLL-AuNPs showed similar variation in charge and binding affinity to plasma proteins in comparison with PVA-AuNPs. However, PLL-AuNPs.protein complexes revealed a drastic change in size compared to the other tested particles. Results obtained from the neutrophil function test and pyridine formazan extraction revealed the highest activation level of neutrophils (~70%) by 50  μ g/mL of PLL-AuNPs compared to a null induction by PEG- and PVA-AuNPs. This observation was further verified by flow cytometry analysis of polymorphonuclear cell size variation in the presence of coated AuNPs. Overall, our in vivo -like method, to test for NP immunorecognition, proved to be reliable and effective. Finally, our data supports the use of PEG-AuNPs as promising vehicles for drug delivery, as they exhibit minimal protein adsorption affinity and insignificant charge and size variation once introduced in whole blood.